2003
DOI: 10.1152/ajpregu.00002.2002
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of sympathetic nerve traffic and BP at very low frequencies is mediated by large-amplitude events

Abstract: This study explores the functional association between renal sympathetic nerve traffic (NT) and arterial blood pressure (BP) in the very-lowfrequency range (i.e., Ͻ0.1 Hz). NT and BP (n ϭ 6) or BP alone (n ϭ 17) was recorded in unanesthetized rats (n ϭ 6). Data were collected for 2-5 h, and wavelet transforms were calculated from data epochs of up to 1 h. From these transforms, we obtained probability distributions for fluctuation amplitudes over a range of time scales. We also computed the cross-wavelet power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…More recently, our group (7) reported that arterial BP and sympathetic nerve activity (SNA) signals did not conform precisely to stationary 1/f noise, at least within the frequency range between 0.02 and 2.0 Hz in the unanesthetized rat. We found that intermittent "large-amplitude events" are important contributors to the very low-frequency variability in these signals (6). With this caveat, the dynamic behavior of HR, BP, and SNA generally displays self-similar behavior below 0.4 Hz.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…More recently, our group (7) reported that arterial BP and sympathetic nerve activity (SNA) signals did not conform precisely to stationary 1/f noise, at least within the frequency range between 0.02 and 2.0 Hz in the unanesthetized rat. We found that intermittent "large-amplitude events" are important contributors to the very low-frequency variability in these signals (6). With this caveat, the dynamic behavior of HR, BP, and SNA generally displays self-similar behavior below 0.4 Hz.…”
mentioning
confidence: 73%
“…Spectral power within the range from 0.35 to 0.45 Hz was computed with fast Fourier transform procedures described in detail elsewhere (4). Likewise, procedures for the wavelet computation have been described elsewhere (6,10). Briefly, the wavelet transform of a time series x(t) is defined as…”
Section: Subjectsmentioning
confidence: 99%
“…those produced by myogenic responses originating in regional circulations (Létienne et al 1998). Therefore, slow RSNA fluctuations comprise both baroreflex-and non-baroreflex-mediated RSNA variations (Burgess et al 2003).…”
Section: Sympathetic Neural Discharge In Rats (A ) General Consideratmentioning
confidence: 99%
“…Burgess et al 2 showed that cross spectrum analysis using wavelet transform characterized strong coupling between sympathetic nerve traffic and AP at frequencies of <0.1 Hz. Davrath et al 4 reported that timevarying power obtained from wavelet transform of the spontaneous HR or AP fluctuation in humans are remarkably modulated at approximately 0.1 Hz under standing condition.…”
Section: Time-series Analysis For Dynamic Baroreflexmentioning
confidence: 99%